2014
DOI: 10.1155/2014/602197
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Biochar on Physical Properties and Erosion Potential of a Mudstone Slopeland Soil

Abstract: Food demand and soil sustainability have become urgent issues recently because of the global climate changes. This study aims to evaluate the application of a biochar produced by rice hull, on changes of physiochemical characteristics and erosion potential of a degraded slopeland soil. Rice hull biochar pyrolized at 400°C was incorporated into the soil at rates of 2.5%, 5%, and 10% (w/w) and was incubated for 168 d in this study. The results indicated that biochar application reduced the Bd by 12% to 25% and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 46 publications
8
48
3
Order By: Relevance
“…The results of statistical analyses (Table 7) demonstrated a significant effect at p b 0.1 level on soil loss (p-value = 0.057) as well as a significant effect at p b 0.05 level on sediment concentration (p-value = 0.010) due to biochar application, as similarly reported by Jien and Wang (2013) and Hseu et al (2014) for the application of biochar produced from waste wood and rice hull. In addition, Liu et al (2012) reported that the soil aggregate sizes and stability significantly increased due to the addition of 4, 8, and 16 g kg −1 biochar to the soil, especially for a silt loam soil in the Loess Plateau in China.…”
Section: Effect Of Biochar On Soil Loss and Sediment Concentrationsupporting
confidence: 69%
See 2 more Smart Citations
“…The results of statistical analyses (Table 7) demonstrated a significant effect at p b 0.1 level on soil loss (p-value = 0.057) as well as a significant effect at p b 0.05 level on sediment concentration (p-value = 0.010) due to biochar application, as similarly reported by Jien and Wang (2013) and Hseu et al (2014) for the application of biochar produced from waste wood and rice hull. In addition, Liu et al (2012) reported that the soil aggregate sizes and stability significantly increased due to the addition of 4, 8, and 16 g kg −1 biochar to the soil, especially for a silt loam soil in the Loess Plateau in China.…”
Section: Effect Of Biochar On Soil Loss and Sediment Concentrationsupporting
confidence: 69%
“…Based on these results, a 5% application rate of biochar was considered as suitable for highly weathered soil of southern Taiwan. Meanwhile, Hseu et al (2014) indicated that biochar application could significantly reduce soil loss contents by 35% to 90% under an extreme rainfall event in the degraded mudstone soil. They also reported that the enhancement of soil strength might be the major factor in decreasing the soil loss in the biochar-amended soil.…”
Section: Effect Of Biochar On Soil Loss and Sediment Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…From our microstructure observation (Figure 4), a mechanism of SOM stabilization by biochar addition could be deduced as follows: soil structure was changed and some macro-aggregate were formed after biochar incorporation (Figure 4a;4b), which was also provided by our previous studies [38,39]. The formation of the new aggregates wrapped the biochar and compost in the aggregates, and therefore might prevent from rapidly decomposing by microbes (Figure 4c-f).…”
Section: Co2 Emissions From Soils Amended With the Compost And Biocharssupporting
confidence: 57%
“…Soil crusting is common on the surface of this badland soil, which increases its bulk density and penetration resistance. Previous research4 has indicated that root growth could be inhibited when penetration resistance exceeds 14 kg cm −2 , where the penetration resistance of the bare soil in the badlands of Southern Taiwan has been shown to be high (14.5 ± 1.47 kg cm −2 )5.…”
mentioning
confidence: 99%